2014
DOI: 10.1016/j.bushor.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Customer co-creation projects and social media: The case of Barilla of Italy

Abstract: This article investigates a social media-enabled, customer co-creation project that employs front-end innovation (FEI) at a well-known, large-scale food manufacturer. It sheds light on the role of social media technology in transforming the characteristics of FEI in terms of boundaries and knowledge distance. What type of exploratory or exploitative innovation ideas does a project of this sort enable? How did the project evolve? What lessons can be learned from this project? A longitudinal case study of Barill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 12 publications
(11 reference statements)
1
35
0
4
Order By: Relevance
“…Such interactions, in addition to providing increased utility to customers, are information rich for firms, which naturally leads to a higher chance of acquiring useful insights for product innovation. This observation of stronger positive effects on the innovative function of deep involvement with consumers is consistent with previous case study research identifying multiple benefits of engaging customers through highlyinteractive Web 2.0 tools, both in terms of innovation and day-to-day business operations [Martini et al, 2014;Martinez Garcia, 2013]. Notably, the two cited papers investigated food and beverage industry firms (the same as the manufacturers in our study), making it more likely that our findings are quantitative reflections of similar underlying mechanisms.…”
Section: Discussionsupporting
confidence: 78%
“…Such interactions, in addition to providing increased utility to customers, are information rich for firms, which naturally leads to a higher chance of acquiring useful insights for product innovation. This observation of stronger positive effects on the innovative function of deep involvement with consumers is consistent with previous case study research identifying multiple benefits of engaging customers through highlyinteractive Web 2.0 tools, both in terms of innovation and day-to-day business operations [Martini et al, 2014;Martinez Garcia, 2013]. Notably, the two cited papers investigated food and beverage industry firms (the same as the manufacturers in our study), making it more likely that our findings are quantitative reflections of similar underlying mechanisms.…”
Section: Discussionsupporting
confidence: 78%
“…One benefit of collaboration through digital platforms is that it allows firms to engage, more than ever before, in timely and direct end users contact at a relatively lower cost and higher efficiency than the traditional communication tools [41,42].…”
Section: Social Media Social Learning and Value Co-creationmentioning
confidence: 99%
“…Various industries (Finland) [16] Knowledge creation process, knowledge sharing A case of IT and multimedia business (Japan) [21] Knowledge sharing Mobile service (Nokia Group (Finland) [26] Knowledge sharing A case of food manufacturing company (Italy) [28] Social network -Networking Telecommunication projects (Multiple nations) [5] Social network Research institutes in Biomedicine (N/A) [30] Social structure Space industry (Multiple nations) [22] Communication, virtuality Electronic products (The Netherlands) [23] Goal role of the creation process presented by the SECI is also explored. It should be noted that the current research did not consider the patent variable, although some of the reviewed literature used it to describe the CP in the context of Taiwan (Table 1) [46,48,49].…”
Section: Knowledge Cpmentioning
confidence: 99%
“…With a relevant creation process presented by SECI [33], members or customers can collaboratively construct new knowledge based on the knowledge that other members possess through communication and interaction [2,26,28]. For example, Mahr and Lievens [26] reported that community users prefer explicit knowledge that members provided, which can be easily integrated into the development of new products or services.…”
Section: Introductionmentioning
confidence: 96%